Effectiveness and Safety of Anti-interleukin-17 Therapies in Elderly Patients with Psoriasis - Céline Phan; Nathalie Beneton; Juliette Delaunay; Ziad Reguiai; Claire Boulard; Anne-Claire Fougerousse; Elisa Cinotti; Marco Romanelli; Laure Mery-Bossard; Domitille Thomas-Beaulieu; Josiane Parier; François Maccari; et al. (Medical Journals Sweden, 2020)
Anti-interleukin-17 agents have recently been developed for the treatment of psoriasis. This study evaluated the tolerance and effectiveness of anti-interleukin-17 agents for psoriasis in elderly patients in daily practice. A multicentre, retrospective study was performed, involving psoriatic patients aged ≥65 years who had received an anti-interleukin-17 agent, including secukinumab, ixekizumab or brodalumab. A total of 114 patients were included: 72 received secukinumab, 35 ixekizumab, and 7 brodalumab. Treatment was stopped in 32 patients (28.9%), because of relapses in 14 patients (41.2%), primary failures in 11 patients (32.4%), or adverse events in 7 patients (20.6%). The 3 most frequently reported adverse events were injection site reactions (n = 4), oral candidiasis (n = 3), and influenza-like illness (n = 3). Regarding effectiveness, 80 patients (70%) reached a Physician Global Assessment score of 0/1, 6 months after treatment initiation. In conclusion, anti-interleukin-17 therapy appears to be an effective and safe therapeutic option for psoriasis treatment in patients aged ≥ 65 years.